How not to look old : fast and effortless ways to look 10 years younger, 10 pounds lighter, 10 times better - Krupp, Charla (Springboard Press, 2008)
"Boot camp for a younger, hipper makeover, packed with no-holds-barred advice on little beauty and fashion changes that pay off big time."--Provided by the publisher.